Jula-Jula: Economic and Accounting Practices in the Muslim Community of North Sumatra - Kamilah Kamilah; Ahmad Muhaisin B Syarbaini; Muhammad Yafiz (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
This study aims to analyze and evaluate jula-jula as an accounting and economic practice among the Muslim population of North Sumatra. This study is a descriptive qualitative evaluation of indigenous knowledge in North Sumatra. In-depth interviews were employed for data gathering. Four jula-jula practitioners, five academics, and four Islamic scholars (ulama) were chosen as informants using the snowball sampling technique. The analysis was conducted using Miles and Huberman’s model starting from data reduction, data presentation, to conclusion drawing. The findings illuminate the relationship between jula-jula as an accounting and economic practice and cultural accounting, managerial accounting, behavioral accounting, and Islamic economics. The findings provide a solution for accounting and sharia-based public financial planning.==============================================================================================================ABSTRAK - Jula-Jula: Praktik Akuntansi dan Ekonomi dalam Komunitas Masyarakat Muslim Sumatera Utara. Penelitian ini bertujuan untuk menggali dan mereview jula-jula, kearifan lokal di Sumatera Utara sebagai suatu praktik akuntansi dan ekonomi dalam komunitas masyarakat muslim Sumatera Utara. Penelitian ini merupakan penelitian deskriptif kualitatif, dengan mempelajari keadaan objek penelitian yakni jula-jula suatu kearifan lokal di Sumatera Utara menggunakan wawancara mendalam sebagai metode pengumpulan data. Pemilihan informan dilakukan dengan cara snowball sampling. Informan terdiri dari lima orang akademisi, empat orang ulama dan empat orang praktisi. Selanjutnya dianalisis dengan model Miles dan Huberman mulai dari reduksi data, penyajian data dan pengambilan kesimpulan. Temuan penelitian ini berkontribusi dalam memahami hubungan praktik jula-jula sebagai praktk akuntansi dan ekonomi dengan akuntansi budaya, akuntansi manajemen, akuntansi keprilakuan dan ekonomi syariah. Penelitian ini dapat menjadi solusi dalam perencanaan keuangan masyarakat yang sesuai dengan akuntansi dan kaidah syariah.